2014
DOI: 10.1016/j.toxlet.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed mitochondrial biogenesis in folic acid-induced acute kidney injury and early fibrosis

Abstract: Acute kidney injury (AKI) is a disease with mitochondrial dysfunction and a newly established risk factor for the development of chronic kidney disease (CKD) and fibrosis. We examined mitochondrial homeostasis in the folic acid (FA)-induced AKI model that develops early fibrosis over a rapid time course. Mice given a single dose of FA had elevated serum creatinine (3-fold) and urine glucose (2.2-fold) 1 and 2 d after injection that resolved by 4 d. In contrast, peroxisome proliferator gamma coactivator 1α (PGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 39 publications
3
94
0
Order By: Relevance
“…Mitochondrial turnover is regulated by a complex interplay between fission/ fusion, autophagy/mitophagy, and MB (Gottlieb and Gustafsson, 2011;Stallons et al, 2013). Our laboratory and others have recently demonstrated alterations in MB in experimental models of AKI (Weinberg, 2011;Funk and Schnellmann, 2012;Jesinkey et al, 2014;Stallons et al, 2014). MB is tightly controlled by the PGC-1 family of transcriptional coactivators including PGC-1a, PGC-1b, and PRC which coordinate both nuclear and mitochondrial responses to increase cellular mitochondrial content.…”
Section: Discussionmentioning
confidence: 97%
“…Mitochondrial turnover is regulated by a complex interplay between fission/ fusion, autophagy/mitophagy, and MB (Gottlieb and Gustafsson, 2011;Stallons et al, 2013). Our laboratory and others have recently demonstrated alterations in MB in experimental models of AKI (Weinberg, 2011;Funk and Schnellmann, 2012;Jesinkey et al, 2014;Stallons et al, 2014). MB is tightly controlled by the PGC-1 family of transcriptional coactivators including PGC-1a, PGC-1b, and PRC which coordinate both nuclear and mitochondrial responses to increase cellular mitochondrial content.…”
Section: Discussionmentioning
confidence: 97%
“…Development of fibrosis in the folic acidinduced AKI model was associated with suppression of mitochondrial biogenesis. 39 Moreover, epigenetic alterations can be activated after kidney injury, including histone modifications, DNA methylation, and chromosomal conformational changes that regulate gene expression. There have been studies showing that histone deacetylase inhibitors accelerate recovery and decrease postinjury fibrosis after I/R 40 and aristolochic acid nephrotoxicity, 41 suggesting that epigenetic changes may influence the transition of AKI to CKD.…”
Section: Question 3 What Are the Relevant Biochemical Pathways Relatmentioning
confidence: 99%
“…16,[19][20][21][22] Recently increasing evidences showed mitochondrial dysfunction in a broad spectrum of pathogenesis of renal diseases. Moreover renal diseases patients exhibited an impaired mitochondrial respiratory system.…”
mentioning
confidence: 99%
“…Tubular epithelial cell damage causes from apoptosis/necrosis and epithelial-mesenchymal transition, additionally, endothelial dysfunction causes from apoptosis/necrosis and endothelial-mesenchymal transition. 18,19,[21][22][23][24][25][26] Studies have shown significantly increased ROS production, up-regulation of TGF-β expressions, high glucose levels, proteinuria, uremic toxins, ischemia/hypoxia, and activation of RAAS in peripheral blood mononuclear cells of patients, thereby demonstrating the close association between mitochondrial dysfunction and renal diseases progression. 21,25,27,28 Recently, a number of studies have revealed that regulation of co-activators can physiologically signal to specific transcription factor targets.…”
mentioning
confidence: 99%
See 1 more Smart Citation